Long term prognosis of children born to lupus patients. Issue 1 (12th December 2003) - Murashima, A; Fukazawa, T; Hirashima, M; Takasaki, Y; Oonishi, M; Niijima, S; Yamashiro, Y; Yamataka, A; Miyano, T; Hashimoto, H
Abstract : Objective: To determine the long term prognosis of children of patients with systemic lupus erythematosus (SLE). Methods: Children of patients with SLE were invited to attend our clinic for physical examination and laboratory tests. A total of 195 children (aged 4 months to 26 years; male = 82, female = 113) were examined in 1991, 1995, 1997, and 1998. Results: Two cases were diagnosed as SLE at the first visit and were excluded from the second visit. A significantly higher percentage (52/195 (27%)) of patients were positive for antinuclear antibodies (ANA) at a cut off serum dilution of 1/40 compared with controls (4/57 (7%)). ANA were detected more frequently in female subjects than in men (p<0.05). Forty four subjects were examined on more than two occasions. Nine of the 10 patients who were positive for ANA at the second visit were girls aged 4–8 years. The incidence of anti-DNA and antiphospholipid antibodies in children of patients with SLE was similar to that in the controls. Conclusions: The finding that children, especially girls, born to maternal lupus patients had a high positive rate for ANA suggests that a genetic factor is involved in SLE pathogenesis. Longitudinal observation of these patients may provide important clinical information and clues to the pathogenesis of SLE.